2020
DOI: 10.1111/jfbc.13564
|View full text |Cite
|
Sign up to set email alerts
|

Regulation effects of indigestible dietary polysaccharides on intestinal microflora: An overview

Abstract: The human intestinal contains rich and diverse microbiota that utilizes a variety of polysaccharides. The intestinal microflora extends the metabolic functions of the body, obtaining energy from indigestible dietary polysaccharides. It is not only a highly competitive environment but also a comprehensive collaboration for these polysaccharides, as the microbiota work to maximize the energy harvested from them through the intestine. Indigestible dietary polysaccharides help to manage colon health and host healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 93 publications
1
30
0
Order By: Relevance
“… 30 Of interest, it was reported that APS were not easily directly absorbed by the intestine but they did regulate gut microbiota. 14 The current study found that APS had a therapeutic effect on acute colitis induced by sodium dextran sulfate and could restore the structure of gut microbiota. 31 They could also increase the level of 2‐hydroxybutyric acid in the serum and liver of mice by regulating gut microbiota and improve lipid metabolism disorders in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“… 30 Of interest, it was reported that APS were not easily directly absorbed by the intestine but they did regulate gut microbiota. 14 The current study found that APS had a therapeutic effect on acute colitis induced by sodium dextran sulfate and could restore the structure of gut microbiota. 31 They could also increase the level of 2‐hydroxybutyric acid in the serum and liver of mice by regulating gut microbiota and improve lipid metabolism disorders in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 53%
“…Gut microbiota can also affect the lung infiltration of MDSC in melanoma‐bearing mice with a high fat diet and, finally, affect tumor metastasis 30 . Of interest, it was reported that APS were not easily directly absorbed by the intestine but they did regulate gut microbiota 14 . The current study found that APS had a therapeutic effect on acute colitis induced by sodium dextran sulfate and could restore the structure of gut microbiota 31 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Short-chain fatty acids are an important link between the host and gut microbiota, which comprise different bacteria in the intestine, especially anaerobic bacteria, through dietary fibre fermentation ( Kumar et al, 2020 ; Ge et al, 2021 ). SCFAs are organic fatty acids with fewer than six carbon atoms, and acetate, propionate and butyrate are considered the most important and biologically effective ones, accounting for 95% of the SCFAs produced by the gut microbiota ( He et al, 2020 ).…”
Section: Scfas and Blood Pressurementioning
confidence: 99%
“…In addition to alkaloids, polysaccharides and other compounds may be extracted and exist in AA. Many studies have demonstrated that polysaccharides can modulate the composition and function of gut microbiota to regulate energy metabolism [53][54][55][56]. Therefore, Aconite polysaccharides may also be responsible for the therapeutic effect of AA.…”
Section: Discussionmentioning
confidence: 99%